Pemanfaatan Limbah Sampah Organik Rumah Tangga di Kelurahan Kota Baru Kota Bandar Lampung - Dedy Yuliawan; Veronica Wanniatie; Raka Rifaldi Racsyah; Ramadan Putra Agusti; Muhammad Fajar Ramadhan (Jurnal PKM Manajemen Bisnis, 2026)
Household organic waste is a major contributor to environmental pollution when not properly managed. In urban areas like Kota Baru Sub-district, Bandar Lampung City, improper waste disposal practices have resulted in increased waste volume and environmental degradation. This community service program (PKM) aimed to raise public awareness and provide practical knowledge on the utilization of household organic waste through environmentally friendly methods. The activity was conducted in July 2025 at the Kota Baru Sub-district Office, involving seven lecturers and students from the University of Lampung as facilitators, and twenty local residents as participants. The program consisted of educational presentations, practical workshops on making eco-enzyme products, maggot cultivation, and packaging techniques, followed by interactive discussions and a Q&A session. The approach emphasized direct community involvement, hands-on learning, and sustainable waste management practices. As a result, participants showed increased understanding of organic waste management and demonstrated the ability to replicate the techniques independently. Many expressed commitment to apply the knowledge in their households and spread it to their community. This activity not only enhanced environmental awareness but also empowered the community to contribute to waste reduction through simple, low-cost technologies.